Antimicrobial activity of complete denture cleanser solutions based on sodium hypochlorite and Ricinus communis - a randomized clinical study - Marcela Moreira SALLES; Maurício Malheiros BADARÓ; Carolina Noronha Ferraz de ARRUDA; Vanessa Maria Fagundes LEITE; Cláudia Helena Lovato da SILVA; Evandro WATANABE; Viviane de Cássia OLIVEIRA; Helena de Freitas Oliveira PARANHOS (University of São Paulo, 2015)
ABSTRACT To preserve oral health and to maintain the prosthetic devices, it is important not only to improve the properties of commonly known hygiene products, but also to investigate new materials with antimicrobial action. Objectives This study evaluated the antimicrobial activity of sodium hypochlorite (0.25% and 0.50%) and 10% Ricinus communis' solutions against specific microorganisms. Material and Methods Sixty four maxillary complete denture wearers were instructed to brush their dentures three times a day and to soak them (20 min/day) in the solutions: SH1: 0.25% sodium hypochlorite; SH2: 0.5% sodium hypochlorite; RC: 10% R. communis oil; and C: 0.85% saline (control). The solutions were used for 7 days in a randomized sequence. Following each period of use, there was a 1-week washout period. Antimicrobial activity was determined by Colony Forming Units (CFU) counts of Streptococcus mutans, Candida spp., and gram-negative microorganisms. For collecting biofilm, the internal surface of maxillary dentures was brushed with saline solution, and biofilm suspension obtained. After dilutions (100 - 10-3), aliquots were seeded in Mitis salivarius, CHROMagar Candida®, and MacConkey agar for detecting S. mutans, Candida spp., or gram-negative microorganisms, respectively. After incubation, colonies were counted, and CFU/mL values were calculated. Then, transformation - log10 (CFU+1) - data were analyzed using the Friedman test (α=0.05). Results showed significant differences between the solutions (p<0.001). Results All three solutions showed antimicrobial activity against S. mutans. Against Candida spp., RC and SH1 solutions showed similar effect while SH2 showed superior activity. SH1 and SH2 solutions showed antimicrobial action against gram-negative microorganisms. The Candida species most frequently isolated was C. albicans, followed by C. tropicalis and C. glabrata. Conclusions The 0.5% sodium hypochlorite solution was the most effective and might be used to control denture biofilm. C. albicans was the most frequently isolated Candida sp.